2005
DOI: 10.1007/s11175-005-0154-4
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Electrochemical N-Dimethoxyphenylation of 3-Nitro-1,2,4-triazole and Tetrazole

Abstract: Using the obtaining of 1,4-dimethoxy-2-(3-nitro-1,2,4-triazole-1-yl)benzene (I) and 1,4-dimethoxy-2-(tetrazolyl-1+-2)benzene (II) as an example, a method for indirect electrosynthesis of these substances is developed. In the first stage of this process, electrosynthesis of 1,1,4,4-tetramethoxycyclohexane-2,5-diene is realized by means of oxidation of 1,4-dimethoxybenezene on a platinum anode in an environment of MeOH in a diaphragmless cell. In the second, chemical interaction of this diene with 3-nitro-1,2,4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Heating 105 in the presence of 3nitro-1,2,4-triazole or tetrazole yielded ortho-substituted species 102. 151 This indirect electrolysis strategy helped to decrease undesired side product formation.…”
Section: Azolationssupporting
confidence: 80%
See 2 more Smart Citations
“…Heating 105 in the presence of 3nitro-1,2,4-triazole or tetrazole yielded ortho-substituted species 102. 151 This indirect electrolysis strategy helped to decrease undesired side product formation.…”
Section: Azolationssupporting
confidence: 80%
“…Interested in the mechanistic underpinnings of these electrochemical azolation reactions, the research group of Petrosyan et al has performed extensive studies to elucidate a reaction mechanism. From these studies, the authors have developed a probable mechanistic pathway for the electrochemical azolation of 88 and related arenes (Scheme ). , It was found that the mechanism for azolation depends significantly on the acidity or basicity of the azole species.…”
Section: Coupling Reactionsmentioning
confidence: 99%
See 1 more Smart Citation